Flora diversity and soil nutrients in samudra university arboretum: development of a conservation learning module based on environmental and climate education - Jayanthi, Sri; Arico, Zulfan; Achmmad Mustaqim, Wendy; Saudah, Saudah (Biosfer: Jurnal Pendidikan Biologi, 2025)
Climate change has long been an important global issue caused by large-scale environmental changes. In the context of green spatial planning, arboretums are important elements that contribute to improving the quality of urban environments and maintaining the balance of local ecosystems. This study aims to explore the flora diversity of the Samudra University Arboretum and analyze soil macronutrient content to assess the relationship between soil fertility levels and the vegetation growing on it. These findings are expected to be utilized as contextual learning media in biology education on environment, ecosystem and biodiversity materials that will foster understanding and awareness of the importance of protecting the environment, conservation, sustainable spatial management, introduction to the impacts of climate change. Observations were made using the inventory method, with data analysis focused on the content of macro nutrients in the soil taken from the arboretum land. The research location was at the Ocean University Arboretum, the research was conducted in June-November 2023. From the results of the study found 16 species with a total of 437 individuals. The most abundant species was Alysicarpus vaginalis with 92 individuals, followed by Ottochloa arnottiana with 55 individuals and Spermacoce sp. with 45 individuals. The species with the highest cover were Alysicarpus vaginalis and Digitaria sp., each at 220%, indicating significant dominance in the observed plant community. From the results of this study, it is recommended that schools, especially at the middle and high school levels, integrate visits and learning activities at the arboretum into the biology curriculum, because the arboretum can function as an outdoor natural laboratory that supports hands-on understanding of biodiversity, ecology, morphology, and plant conservation.